1987
DOI: 10.1144/gsjgs.144.4.0569
|View full text |Cite
|
Sign up to set email alerts
|

Age of Feiran basement rocks, Sinai: implications for late Precambrian crustal evolution in the northern Arabian–Nubian Shield

Abstract: Abstrart: Basement exposed on the perimeter of the Red Sea was created during the Pan-African event at the end of the Precambrian. Pre-Pan-African crust in the northern part of this region has not yet been identified. This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(62 citation statements)
references
References 31 publications
7
55
0
Order By: Relevance
“…A Sr i locality map including data from this study and the literature (Azer et al 2009;Beyth et al 1994;Katzir et al 2007a, b;Moghazi et al 1998;Mushkin et al 2003;Stein and Goldstein 1996;Stern and Manton 1987) is shown in Fig. 3c.…”
Section: Whole-rock Sr-nd Isotope Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…A Sr i locality map including data from this study and the literature (Azer et al 2009;Beyth et al 1994;Katzir et al 2007a, b;Moghazi et al 1998;Mushkin et al 2003;Stein and Goldstein 1996;Stern and Manton 1987) is shown in Fig. 3c.…”
Section: Whole-rock Sr-nd Isotope Resultsmentioning
confidence: 72%
“…A younger tectono-magmatic phase in this region includes the weakly to non-metamorphosed Feirani-Rutig volcano-sedimentary series and minor calc-alkaline deformed plutons of *675-640 Ma (CA1 suite; Eyal et al 1991;Jarrar et al 2003;Kröner et al 1990;Moussa et al 2008;Stern and Hedge 1985;Stern and Manton 1987).…”
Section: Geology Of the Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…38-60 km equivalent elastic thickness of the lithosphere of Arabian Platform, the age of which is estimated between 600 and 900 Ma (e.g. Stern & Manton 1987;Hargrove et al 2006), is in the ballpark of values found for other continental areas with similar Neoproterozoic age (Burov 2011;Tesauro et al 2013). This range of values informs us about the rheology of the continental lithosphere and, in particular, about the mechanical coupling between the crust and mantle, which controls where the strength of the continental lithosphere resides (Burov & Diament 1992;Watts & Burov 2003;Burgmann & Dresen 2008).…”
Section: Implications For the Rheological Layering Of The Continentalmentioning
confidence: 77%
“…The dyke intrusion was occurred during the second stage of the shield formation. The dykes swarms have been investigated in Jordan by Jarrar et al (1992) and Zaineldeen et al (2002), in Saudi Arabia by Jackson et al (1984), in southern Israel by Beyth et al (1994Beyth et al ( , 1995 and Kessel et al (1998), in Sinai by Friz-Töpfer (1991), Stern and Manton (1987) and in Eastern and Western deserts of Egypt by Stern and Gottfried (1986), Stern and Voegeli (1987), Stern et al (1988), Pudlo and Franz (1994).…”
Section: Introductionmentioning
confidence: 99%